Efficacy of ethrel (2-chloroethyl phosphonic acid) as a chemical hybridizing agent in red pepper (Capsicum annuum L. var. Pusa jwala) - Agnihotri, D. K.; Chauhan, S. V. S. (International Journal of Horticultural Science, 2007)
A field experiment was conducted during 2003-2004 and 2004-2005 to study the effect of foliar sprays of ethrel or ethephon (2- chloroethyl phosphonic acid) on pollen sterility and yield parameters in Capsicum annuum var. Pusa jwala. Effect of treatments was also studied in F1 hybrids raised from treated male sterile plants crossed with the control plants. Plants sprayed with 0.1, 0.2 and 0.3% (v/v) ethrel exhibited 93.1-100% pollen sterility. This was associated with significant reduction in yield parameters (number of flowers, fruits/plant, fruit size, number of seeds/fruit and total yield/plant). However, the plants sprayed only once with 0.1% ethrel at pre-meiotic stage showed 93.1% pollen sterility without any significant reduction in yield parameter. The F1 hybrids obtained by crossing the 100% male sterile treated plants with the pollen of untreated (control) plants exhibited only insignificant reduction in the number of flowers/ plant, fruits/plant, fruit size, number of seeds/fruit and total yield/plant. However, these parameters in F1 hybrids were significantly higher over the treated plants.